1985
DOI: 10.1016/s0006-3495(85)83917-5
|View full text |Cite
|
Sign up to set email alerts
|

Transient dichroism in photoreceptor membranes indicates that stable oligomers of rhodopsin do not form during excitation

Abstract: If a photoexcited rhodopsin molecule initiates the formation of rhodopsin oligomers during the process of visual excitation, the rate of rotational diffusion of the rhodopsin molecules involved should change markedly. Using microsecond-flash photometry, we have observed the rotational diffusion of rhodopsin throughout the time period of visual excitation and found that no detectable change occurs in its rotational diffusion rate. Partial chemical cross-linking of the retina yields oligomers of rhodopsin and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…aggregation, and not inclusion body formation, that underlies FALS and perhaps other aggregation-linked neurodegenerative diseases. The oligomeric forms of rhodopsin, much like those of SOD, are non-native structures, given the fact that the wild-type is monomeric (33). Thus, they fit our definition of aggregates, being "non-native oligomers.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…aggregation, and not inclusion body formation, that underlies FALS and perhaps other aggregation-linked neurodegenerative diseases. The oligomeric forms of rhodopsin, much like those of SOD, are non-native structures, given the fact that the wild-type is monomeric (33). Thus, they fit our definition of aggregates, being "non-native oligomers.…”
Section: Discussionmentioning
confidence: 89%
“…Aggresome formation by P23H does not require proteasome inhibitors, because they are observed in cells in the absence of any drug treatment. Second, because FRET is efficient only for C/YFP fluorophores that are within 100 Å of each other (54), our data suggest that the P23H mutation endows the rhodopsin molecule, normally a monomer even at the high concentrations present within the rod outer segments (33), with the ability to self-associate into compact structures. Finally, we observe identical patterns of electrophoretic motilities of P23H rhodopsin when the cells are lysed in the presence of alkylating agents such as iodoacetamide, which prevent the formation of non-native disulfide-linked species in the highly oxidizing environment of SDS-PAGE (55).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Early studies using rhodopsin, 17,18 muscarinic, 19 and ␤-adrenergic 20 receptors as model GPCRs suggested that GPCRs exist primarily as monomers, although modification of the detergent extraction systems used for protein purification led early investigators to suggest that a varying fraction of GPCRs may also be present in oligomeric form. 19,20 Much recent work using coimmunoprecipitation and resonance energy-transfer techniques have convincingly demonstrated that dimeric GPCR structures are present at the plasma membrane and are the topic of several recent reviews.…”
Section: Oligomerizationmentioning
confidence: 99%
“…In most of these studies, photoactivation of rhodopsin did not affect the results (see also ref. [56]), suggesting that this lack of pre-organization did not change upon activation of rhodopsin.…”
Section: Introductionmentioning
confidence: 98%